The importance of small airways inflammation control in the course and therapy of bronchial asthma - Płusa, Tadeusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Changes in the structure and function of the small airways (< 2 mm diameter) play a major role in airflow limitation in bronchial asthma. Features of cellular inflammation, consisting of an infiltrate rich in lymphocytes and eosinophils, are present in the small airways of patients with asthma. It is suggested that inflammation in the small airways may be responsible for severe asthma and symptoms of nocturnal asthma. It was documented that applied inhaled therapy did not give sufficient control of inflammation in the small airways, because anti-inflammatory medicines were able to penetrate only into the middle bronchi. For this reason a new therapy has been proposed to extend the control process into the small airways. New formulations of inhaled corticosteroids with smaller particle aerosols may be more effective in asthma control. The new combination of ultra-fine beclomethasone plus formoterol is more effective than the marketed combinations of fluticasone and salmeterol, and budesonide and formoterol.